The plea : the true story of young Wesley Elkins and his struggle for redemption - Bryan, Patricia L., 1951-; Wolf, Thomas, 1947- (Iowa and the Midwest experience., 2022)
"The Plea starts with a terrible crime. On a moonlit night in 1889, the Iowa farmer John Elkins, and his young wife, Hattie, are brutally attacked and murdered in their bed. Eight days later, their son, eleven-year-old Wesley Elkins, is arrested and charged with the crime. The community is shocked by both the gruesome facts of the homicide and the age of the accused perpetrator, a small, quiet boy weighing just 75 pounds. The Plea tells the story of this crime and its aftermath. Despite his youth and evidence that he had been abused by his parents, Wesley is sentenced to spend the rest of his life in an adult prison. For more than a dozen years, the boy's fate is in the hands of others. His story captures the attention of a divided and transfixed public, raising questions about the criminal justice system and the rights of children. The focus of the narrative is on the legal and societal aspects of the case: Wesley's rehabilitation and remarkable transformation in prison, his plea that his case be reconsidered, the outpouring of support he received from prison wardens, politicians, newspaper editors, and educators. The story of the life of Wesley Elkins becomes an emotional and compelling story of redemption. This is a true story, based on years of meticulous research. All the scenes are based on primary sources: newspaper reports, legal documents, interviews, nonfiction works, memoirs, and personal letters. Bryan and Wolf quote from these materials throughout the book. The Plea is an accessible and fast-moving story that delivers a complete, complex, and nuanced narrative of this horrific crime, shedding light on the legal, social, and political environment of Iowa and the country in the late 1800s and early 1900s"--